Keefektifan Bermain Peran dan Keterampilan Bercerita untuk Meningkatkan Kecerdasan Emosional Anak Usia 5-6 Tahun - Parlinah, Parlinah; Nugroho, Aryo Andri; Handayani, Arri (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
Research problems: (1) is role playing effective to improve emotional intelligence of children aged 5-6 years?, (2) is there a difference in emotional intelligence of children aged 5-6 years before and after role playing?, Research objectives: (1) describe increasing emotional intelligence of children aged 5-6 years through role playing, (2) describing the differences in emotional intelligence of children aged 5-6 years before and after role playing. The type of research used is quasi-experimental research or quasi-experimental design. Based on the results of data analysis and discussion, it can be concluded that statistically after being calculated using SPSS 16.0 for windows there is an effective influence of role playing on the emotional intelligence of children aged 5-6 years, this can be seen based on the results of calculations using SPSS 16.0 for windows by comparing between the t value resulting from t count with the t table value. From the table it is known that the value of the Independent Sample t-test (tcount) is 14,331 and the t table is 2,160 with a p value of 0.000. Because the t-count value t-table or ip value 0.05, it is said that there is an average difference between the emotional intelligence of children aged 5-6 years in the experimental group and the control group. So Ho is rejected and Ha is accepted, which means that there is an effective influence of role playing on the emotional intelligence of children aged 5-6 years and there is a difference before and after role playing on children's emotional intelligence after being calculated using the paired sample test t test with the result 0.00 0.05 then Ha is accepted at TK Muslimat NU Masyithoh 08 Kramatsari Pekalongan City. Besides, the results of the research that the researchers have done can be concluded that role playing can improve the emotional intelligence of children in TK Muslimat NU Masyithoh 08 Kramatsari Pekalongan City.